Coral reef restoration can reduce coastal contamination and pollution hazards - Marina E. Rottmueller; Curt D. Storlazzi; Fabian Frick (Communications Earth & Environment)
Abstract Coral reef restoration can reduce the wave-driven flooding for coastal communities. However, this protection has yet to be assessed in terms of the reduced risk of flood-driven environmental contamination. Here we provide the first high-resolution valuation of the reduction of flood-related land-based environmental pollution provided by potential coral reef restoration. Along Florida’s 460 km-long coral reef-fringed coastline, coral reef restoration could reduce the risk of sewage and petrochemical contamination by preventing the flooding of petroleum storage tank systems (-9%), onsite sewage treatment and disposal systems (-4%), and wastewater treatment plants (-10%). The present value of critical infrastructure protection and contamination prevention benefits provided by coral reef restoration is $3,413,503, with some areas exceeding $1,500,000/km. Annually, 48,403 U.S. gal of petrochemicals, 10,404 GPD of wastewater treatment capacity, equivalent to $281,435, could be protected from flooding, demonstrating that coral reef restoration can provide environmental risk reduction and previously undocumented additional socioeconomic benefits.